2020
DOI: 10.3390/bioengineering7020050
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Monitoring Workflow for Formulation, Fill and Finish Processes

Abstract: Process monitoring is a critical task in ensuring the consistent quality of the final drug product in biopharmaceutical formulation, fill, and finish (FFF) processes. Data generated during FFF monitoring includes multiple time series and high-dimensional data, which is typically investigated in a limited way and rarely examined with multivariate data analysis (MVDA) tools to optimally distinguish between normal and abnormal observations. Data alignment, data cleaning and correct feature extraction of time seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Currently, in addition to backtracking purposes, the recorded process data can be used for process monitoring and fault detection in batch and change-over processes. , A monitoring workflow for the formulation, fill, and finish processes was published . Data-driven batch monitoring in drug product manufacturing for change-over processes has been suggested with a focus on cleaning and sterilization in place (C/SIP) and decontamination .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, in addition to backtracking purposes, the recorded process data can be used for process monitoring and fault detection in batch and change-over processes. , A monitoring workflow for the formulation, fill, and finish processes was published . Data-driven batch monitoring in drug product manufacturing for change-over processes has been suggested with a focus on cleaning and sterilization in place (C/SIP) and decontamination .…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 A monitoring workflow for the formulation, fill, and finish processes was published. 18 Data-driven batch monitoring in drug product manufacturing for change-over processes has been suggested with a focus on cleaning and sterilization in place (C/SIP) 17 and decontamination. 19 The latter work showed that deteriorations could be observed across multiple batches before a failure occurs.…”
Section: Introductionmentioning
confidence: 99%